Menyusun Rencana Pelaksanaan Pembelajaran Melalui Bimbingan Berkelanjutan Untuk Meningkatkan Kompetensi Guru SD Inpres 10/73 Welado Kabupaten Bone - Arsyad Arsyad (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This research is a school action research conducted at SD Inpres 10/73 Welado, Bone Regency. This research aims to improve teacher competence in preparing lesson plans through continuous guidance methods. From the results of the study, it was concluded that (1) Continuous guidance can increase teacher motivation in compiling complete lesson plans. The teacher shows seriousness in understanding and compiling the RPP, especially after receiving guidance on developing/compiling RPP from the researcher. This information was obtained by researchers from observations during interviews and guidance on developing/compiling lesson plans to teachers. (2) Continuous guidance can improve teacher competence in preparing lesson plans. This can be proven from the results of observations which show that there is an increase in teacher competence in preparing lesson plans from cycle to cycle. In the first cycle the average value of the RPP component was 69% and in the second cycle 83%. So, there is an increase of 14% from cycle I.